Reversal effect of quercetin on talazoparib resistance in BRCA1 mutant triple negative breast cancer - Güney Eskiler, Gamze; Çeçener, Gülşah; Egeli, Ünal; Tunca, Berrin (The European Research Journal, 2020)
Objectives: Poly(ADP-ribose) polymerase (PARP) inhibitors have demonstrated an outstanding activity in patients with BRCA-mutated and wild-type breast cancer. However, the identification of resistance mechanisms to PARP inhibitors is a significant clinical challenge in effective treatment. Thus, new therapeutic strategies are urgently needed to overcome resistance. The aim of the current study was to explore the potential effect of quercetin on HCC1937 (BRCA1 mutant) and talazoparib (BMN 673), a PARP inhibitor, resistant HCC1937 (HCC1937-R) triple negative breast cancer cells (TNBC).Methods: We firstly generated BMN 673 resistance HCC1937 cells by continuous exposure to BMN 673 during 6 months. Then, cells were exposed to the different concentration (0-100 µM) of quercetin and the cytotoxic and apoptotic effects of quercetin on these cells were evaluated by WST-1, Annexin V and dual acridine orange-ethidiumbromide (Et-BR) staining.Results: The cell viability of HCC1937 and HCC1937-R cells reduced to 37.1% and 44.2% at a concentration of 100 μM, respectively for 48 h (p < 0.01). Apoptotic rates of HCC1937 and HCC1937-R cells treated with 100 μM quercetin were nearly 56.0% and 46.0%, respectively (p < 0.01). Additionally, theapoptotic morphologicalchanges were observed in these cells. Conclusions: In conclusion, the obtained results suggest that quercetin could potentially be used as an alternative therapeutic strategy in BRCA1 mutant TNBC to overcome acquired BMN 673-resistance.